Characteristics and Population Size Estimation of Female Sex Workers in Bhutan. Issue 10 (October 2021) - Khandu, Lekey; Tobgay, Tashi; Kinley, Kinley; Choida, Ngawang; Tashi, Tshering; Wangdi, Tashi; Tashi, Ugyen; Dechenmo, Dechenmo; Choden, Karma Choden; Tsheten, Tashi; Gyeltshen, Tenzin; Zangmo, Kencho; et al.
Abstract : Background: Knowing the number of persons at risk for sexually transmitted diseases (STDs) and their risk behaviors are needed to allocate limited resources, set targets for prevention and care activities, gauge the reach of programs, and assess their impact. Female sex workers (FSWs) are a population at high risk for STD worldwide; little is known about FSW in Bhutan. Methods: We conducted a community-based survey and population size exercise of FSW in Bhutan. The survey used a hybrid venue-based/peer-referral sampling method. Population size estimation methods were key informant mapping, census and enumeration, unique object multiplier, and capture-recapture. Results: Of 517 women surveyed, 67.5% provided sex for money in the last year. Compared with FSWs at venues, FSWs referred by peers were more likely to have sex with alcohol (80.1% vs. 51.5%, P < 0.001) and more paying partners (mean, 3.5 vs. 2.0; P = 0.001), and less likely to have tested for an STD (28.3% vs. 51.0%, P < 0.001) or have outreach worker contact (27.6% vs. 41.5%, P = 0.007). The estimated number of FSWs in the 9 districts was 353 (95% confidence interval, 345–362). Extrapolation to the whole country projected 597 (417–777) FSWs nationally. Conclusions: Our estimate of the number of FSW in Bhutan corresponds to 0.71% of adult urban women, a figure in line with other countries in South and Southeast Asia. Our data highlight the need for outreach beyond venues where women are employed to reach FSW at higher risk for STD but who have less access to interventions. Abstract : A study of female sex workers in Bhutan estimated their numbers nationally at 597 (417–777). Female sex workers not employed at entertainment centers report a higher risk of sexually transmitted diseases.